Back Cover: Single and Double NH Bond Activation of Ammonia by [Al2O3].+: Room Temperature Formation of the Aminyl Radical and Nitrene (Angew. Chem. Int. Ed. 36/2013). Issue 36 (2nd August 2013) - Kretschmer, Robert; Wang, Zhe‐Chen; Schlangen, Maria; Schwarz, Helmut
<x xml:space="preserve">Abstract</x> The single and double NH bond activation of ammonia is described by H. Schwarz and co‐workers in their Communication on page 9513 ff. They show that if [Al2O3].+ is allowed to take a bath in ammonia, the problem of the room‐temperature generation of nitrene is solved—single hydrogen‐atom transfer and double hydrogen abstraction occur, and NH2 and NH bubble like an aspirin pill in water. Mass spectrometric and theoretical investigations confirm these results.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>